Nigeria and the Search for Political Development: A Historical Analysis - Wali Doho, Ahmed; Abba Abdullahi, Musa; Mijinyawa, Aaron (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Nigeria is endowed with abundant mineral and human resources that can contribute to the development of the country and Africa. As an actor in the international system, Nigeria has the responsibilities of meeting domestic and foreign obligations that can only be achieved through political development with institutionalized values and attitudes, capable of reshaping the political power system. But since 1960, Nigeria has been facing some challenges that have made this goal difficult to achieve. It is against this background that this paper examines some of the problems, which require solutions. The study adopted qualitative research design and content analysis to generate and analyze necessary data. The paper concludes that, Nigeria’s democracy is on a fragile foundation and, therefore, recommends that the country needs a radical deviation from the perceived Western modernization to a centric approach that can accommodate its peculiarities.